1990
DOI: 10.2337/diacare.13.11.1144
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Diabetes in Blacks

Abstract: Diabetes mellitus is more prevalent in the American Black population than in the White population. The prevalence is increasing in Blacks, and there is evidence that it is accompanied by a greater severity of diabetic complications. In addition, mortality figures are higher in Blacks, and Black women are more seriously affected than Black men. Although the reasons for this are unclear, some factors stand out as important. These include obesity, socioeconomic status, and genetics. Obesity is a severe problem in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 18 publications
0
20
1
Order By: Relevance
“…To our knowledge, no PT study has been reported on the effects of PT, without dietary intervention, on body composition of obese, black girls. Since black females are at especially high risk of obesity (18). it is important to evaluate strategies which might help deal with this problem in childhood.…”
Section: Obesity Research Vol 3 No 4 July 1995 305mentioning
confidence: 99%
“…To our knowledge, no PT study has been reported on the effects of PT, without dietary intervention, on body composition of obese, black girls. Since black females are at especially high risk of obesity (18). it is important to evaluate strategies which might help deal with this problem in childhood.…”
Section: Obesity Research Vol 3 No 4 July 1995 305mentioning
confidence: 99%
“…1 Obesity has been identified as a precursor to many chronic diseases and is probably the strongest risk factor for type 2 diabetes. 2,3 It is also well known that compared to their white counterparts, African Americans are disproportionately affected by the burden of type 2 diabetes. [3][4][5][6] Therefore, in African Americans it is crucial to examine weight-related factors early in life in order to prevent chronic disease that may develop in the middle years.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 It is also well known that compared to their white counterparts, African Americans are disproportionately affected by the burden of type 2 diabetes. [3][4][5][6] Therefore, in African Americans it is crucial to examine weight-related factors early in life in order to prevent chronic disease that may develop in the middle years. The 1995 National College Health Risk Behavior Survey (NCHRBS) suggests that the prevalence of at least overweight is 48.7% in African American students compared to 34.6% in white students.…”
Section: Introductionmentioning
confidence: 99%
“…Findings in the Pima Indians (73,84) and the male population enrolled in the Paris Prospective Study (85) similarly indicated that fasting insulin levels (and other measures of insulin secretion and insulin resistance) predict the development of noninsulin-dependent diabetes mellitus independent of obesity. It is unclear to what extent differences in body fat distribution, the level of obesity, and insulin resistance can explain the marked differences in prevalence of non-insulin-dependent diabetes mellitus in populations (67,76,(86)(87)(88)(89).…”
Section: Insulin Resistance and Obesity In The Pathogenesis Of Non-inmentioning
confidence: 99%